2020
DOI: 10.1108/ijoem-08-2019-0658
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and innovation: the importance of competition

Abstract: PurposeThe purpose of this study is to examine how corruption affects the prevalence of product and process innovation by firms.Design/methodology/approachThis study uses firm-level data from the 2012–2016 Business Environment Enterprise Performance Surveys and utilizes a conditional mixed process model to address endogeneity concerns, taking bribery as a measure of corruption.FindingsThe study shows that measures of bribery are positively and robustly associated with innovation but mainly for firms reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…The present study confirms that corruption impedes process innovation in organizations (Goel and Nelson, 2018). The impact of corruption ( H3 ) on companies operating in higher GDP countries, found in this study, may fit the explanation offered by Karaman Kabadurmus and Sylwester (2022) who argue that in more competitive environments, corruption can help organizations to get around costly regulations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present study confirms that corruption impedes process innovation in organizations (Goel and Nelson, 2018). The impact of corruption ( H3 ) on companies operating in higher GDP countries, found in this study, may fit the explanation offered by Karaman Kabadurmus and Sylwester (2022) who argue that in more competitive environments, corruption can help organizations to get around costly regulations.…”
Section: Discussionsupporting
confidence: 79%
“…Chowdhury et al ’s (2018) findings, using a sample of emerging international start-ups, suggest that corruption plays a “greasing” role when indirect taxes are high, and a “sanding” role when documenting requirements for export, cost of export and corporate tax are high. Notwithstanding the findings listed before, research on the link between corruption and innovation is comparatively underdeveloped (Karaman Kabadurmus and Sylwester, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We observe in column 2 of Table 9 that the coefficient of the cross‐product term between Death and Corruption is −0.035, which is significantly negative at the 1% level, suggesting that increased government efforts to control corruption instead slow down the contribution of natural disasters to the greening of innovation type. Kabadurmus and Sylwester (2022) showed that corruption promotes innovation by allowing firms to evade regulatory barriers. We reach a similar conclusion.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The findings indicate that compared to their male counterparts, on average, women receive a greater payoff from bribery. Karaman Kabadurmus and Sylwester (2020) investigated the role of competition in the corruption–innovation relationship using firm‐level data from the 2012–2016 business environment enterprise performance surveys. Their results show that all measures of bribery are positively associated with innovation especially for firms reporting many competitors and obstacles.…”
Section: Literature Reviewmentioning
confidence: 99%